Synthesis of Mesoporous TiO2 Spheres via the Solvothermal Process and Its Application in the Development of DSSC - S. Velázquez-Martínez; S. Silva-Martínez; A. E. Jiménez-González; A. Maldonado Álvarez (Advances in Materials Science and Engineering)
This study examined the synthesis of the n-type nanostructured titanium dioxide semiconductor using a combined sol-gel/solvothermal method at 200°C, varying the concentrations of H2O and HCl used as a catalyst for the hydrolysis of the titanium isopropoxide precursor. A white powder of TiO2 nanoparticles was obtained via the solvothermal process. Scanning electron microscopy revealed a spherical morphology of the TiO2 nanoparticles, with their diameter ranging from 2 to 7 microns as the HCl concentration increases. High-resolution electron microscopy and X-ray diffraction showed that the spheres are mesoporous titanium oxide (TiO2m) composed of nanocrystals with an anatase crystalline phase whose crystallite diameter grows from 8 to 13 nm as the HCl concentration increases. On the contrary, optimizing the H2O concentration enabled a decrease in the crystallite size of TiO2m and increases in the surface area and the energy band gap of TiO2m. The enlarged surface area enabled an increase in the number of contact points between TiO2m and the dye of dye-sensitized solar cells (DSSCs), resulting in a better solar cell performance. The white powder was used to prepare a TiO2m film via the screen-printing technique, which was used in the development of DSSC. The performance parameters of the DSSC (ISC, VOC, FF, and η%) were correlated with the synthesis parameters of TiO2m. This correlation showed that H2O and HCl greatly influence the semiconductor properties of TiO2m, along with the short-circuit current JSC and the conversion efficiency η% of the DSSC.